L. B. M. Mennes, Jan Tinbergen y J. George Waardenburg. The element of space in development planning. Amsterdam ; Londres : North Holland Publishing Co., 1969. 345 p. - Carrillo Arronte, Ricardo (Estudios Demográficos y Urbanos, 1971)
L. B. M. MENNES, JAN TINBERGEN y J. GEORGE WAARDENBURG, The Element of Space in Development Planning. Amsterdam-Londres, North Holland Publishing Co., 1969.